ChemInform Abstract: Synthesis of Divalent Europium Borate via in situ Reductive Techniques. Issue 38 (30th August 2013) - Polinski, Matthew J.; Cross, Justin N.; Villa, Eric M.; Lin, Jian; Alekseev, Evgeny V.; Depmeier, Wulf; Albrecht‐Schmitt, Thomas E.
Abstract Eu[B8O11(OH)4], is prepared by two in situ reductive methodologies.